Ethnicity and Syndrome X. - Das, Mithun; Bose, Kaushik, 1962- (Nova Science Publishers, Incorporated, 2020)
"The syndrome X or metabolic syndrome may be defined as a constellation of several interrelated risk factors of metabolic origin which includes centrally distributed obesity, decreased high density lipoprotein cholesterol, elevated triglycerides, elevated blood pressure and hyperglycemia. Persons with syndrome X are at twice the risk of developing cardiovascular disease, and are at about five-fold the risk of type 2 diabetes mellitus as compare to persons with this syndrome. There are considerable evidences of important ethnic differences in the prevalence of syndrome X, its components and sequelae. The prevalence varied between ethnic groups even within the same geographical location. Apart from multifactorial (genetic vs. environmental) nature, there are intriguing metabolic and anthropometric differences found across different ethnic groups. The estimates vary by ethnicity, for instance, high prevalence in non-European groups such as Black African-Caribbeans, Hispanics, indigenous populations of North America, South Asians, and the Western Pacific Region and lower prevalence in Chinese populations, and European-White. Public health strategies that are well known to be important for chronic disease prevention in general can substantially reduce the prevalence of syndrome X. Population-specific studies will be important in identifying subgroups for which syndrome X is a health issue and for which disease management strategies are needed. Simultaneously, studies to identify different biomarkers associated with syndrome X that are linked with the development of specific chronic diseases, such as CVD and diabetes, will significantly enhance the early detection of these diseases. Existing preventions strategies, if implemented in population subgroups at highest risk, may have a substantial effect on reducing these trends. The prevalence of syndrome X increases with advancing age suggests that the efforts to increase awareness of prevention strategies must begin early. Intensive treatment and effective targeting efforts would help in avoiding future sequelae of syndrome X across different ethnicity. This book will be an assemblage of similarities and differences in the risk of syndrome X and related disorders among different ethnic groups worldwide, and reviews potential mechanisms for ethnic differences. It would certain help in translational research for early intervention and better prevention of syndrome X and its associated public health burden worldwide"-- Provided by publisher.
Description based upon print version of record.
Effect of Human Migration on Hypertension, Cardiovascular Diseases, Type 2 Diabetes and Their Associations with Metabolic Syndrome among the Asian Indians
Keywords: Human chromosome abnormalities.; Genetic disorders.; Chromosome abnormalities.; Genetic screening.; Genetic Diseases, Inborn; Chromosome Aberrations; Genetic Testing; Chromosomes humains -- Anomalies.; Maladies génétiques.; Aberrations chromosomiques.; Dépistage génétique.; Chromosome abnormalities; Genetic disorders; Genetic screening; Human chromosome abnormalities